2010
DOI: 10.1161/hypertensionaha.110.161521
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial and Plasma Adenosine Stimulate Nitric Oxide and Prostacyclin Formation in Human Skeletal Muscle

Abstract: Abstract-One major unresolved issue in muscle blood flow regulation is that of the role of circulating versus interstitial vasodilatory compounds. The present study determined adenosine-induced formation of NO and prostacyclin in the human muscle interstitium versus in femoral venous plasma to elucidate the interaction and importance of these vasodilators in the 2 compartments. To this end, we performed experiments on humans using microdialysis technique in skeletal muscle tissue, as well as the femoral vein, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(60 citation statements)
references
References 34 publications
2
58
0
Order By: Relevance
“…ATP and adenosine have been known to induce vasodilation following release from the erythrocytes via production of nitric oxide and prostacyclin (Nyberg et al 2010;Sprague et al 2011), and it has been recently demonstrated that exogenous ATP supplementation is capable of increasing exercise-induced blood flow (Jäger et al 2014). Improved blood flow may increase nutrient delivery.…”
Section: Discussionmentioning
confidence: 99%
“…ATP and adenosine have been known to induce vasodilation following release from the erythrocytes via production of nitric oxide and prostacyclin (Nyberg et al 2010;Sprague et al 2011), and it has been recently demonstrated that exogenous ATP supplementation is capable of increasing exercise-induced blood flow (Jäger et al 2014). Improved blood flow may increase nutrient delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the proteins measured in our study are known to be endothelial cell specific, 17,22,24,28,32 and it is likely that the protein levels assessed in the muscle primarily reflected levels in microvascular endothelial cells, but with a potential contribution from other cells associated with the interstitium, including skeletal muscle cells. As our intention was to determine protein levels of vasoactive systems in cells that can contribute to the muscle interstitial levels of vasoactive compounds, determination in muscle biopsies seemed to be the most appropriate.…”
Section: Methodological Considerationsmentioning
confidence: 94%
“…Recently, extracellular production of adenosine, resulting from the degradation of adenine nucleotides via ecto 5=-nucleotidase, has been shown to contribute to rapid vasodilation after electrically stimulated contraction of the hamster cremaster muscle (59). Previous evidence also suggests that adenosine is capable of stimulating NO and PG production in humans (52,57). It is also possible that ACh, released at the neuromuscular junction, could diffuse to nearby capillaries and stimulate NO and PG production (25).…”
Section: Potential Stimuli For Vasodilation After a Single Muscle Conmentioning
confidence: 99%